2018
DOI: 10.1007/s00011-018-1142-y
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, a significant player of Ataxia–Telangiectasia pathogenesis?

Abstract: Ataxia-Telangiectasia Mutated (ATM), a master regulator of the DNA damage response is the protein known to be associated with A-T and has a complex nuclear and cytoplasmic role. Loss of ATM function may induce immune deregulation and systemic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 155 publications
0
28
0
Order By: Relevance
“…They manifest radiosensitivity, sterility, and immunodeficiencies with an elevated risk of developing autoimmune diseases such as arthritis, vitiligo, or immune thrombocytopenia [104]. Authors have also suggested that A-T patients may suffer from prolonged chronic inflammation [94]. Consistent with this, high levels of pro-inflammation cytokines are present in their serum even in the absence of infections [51,52].…”
Section: Molecular Basis For Ataxia Telangiectasia Syndromementioning
confidence: 93%
See 3 more Smart Citations
“…They manifest radiosensitivity, sterility, and immunodeficiencies with an elevated risk of developing autoimmune diseases such as arthritis, vitiligo, or immune thrombocytopenia [104]. Authors have also suggested that A-T patients may suffer from prolonged chronic inflammation [94]. Consistent with this, high levels of pro-inflammation cytokines are present in their serum even in the absence of infections [51,52].…”
Section: Molecular Basis For Ataxia Telangiectasia Syndromementioning
confidence: 93%
“…While the complex relationships between DDR and inflammation are beginning to emerge, it is clear that ROS and other types of genomic injuries can elicit a proinflammatory response. As part of DDR, this pro-survival cell response is mediated mostly through ATM and PARP1 [94]. ATM directly binds and phosphorylates IKK-γ (NEMO), the regulatory subunit of the IKK complex that activates NF-kB [41].…”
Section: Other Ddr Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…A taxia-telangiectasia (a-t) is a rare autosomal recessive pleiotropic syndrome characterised by cerebellar ataxia, oculocutaneous telangiectasia, chromosomal instability, radiosensitivity, variable immunodeficiency, oxidative stress and a high risk of malignancy. 1,2 Worldwide, only one in 40,000-100,000 neonates is homozygous for the A-T mutated (ATM) gene mutation; however, 0.5-2% of the general population are heterozygous carriers. 1 Although heterozygous ATM carriers are commonly asymptomatic, they have a higher sensitivity to ionising radiation (IR) and a higher risk of type 2 diabetes mellitus, cardiovascular diseases and cancers.…”
mentioning
confidence: 99%